Protagoras in the Theaetetus: arguments of "defence" and "self-refutation" - Trindade Santos, José Gabriel (Revista Archai, 2024)
Is there an explanation for ‘Socrates’’ wavering attitude towards Protagoras, in the Theaetetus? It seems he praises him only to chide him, though always showing some measure of respect. Can such behaviour be justified by irony? What connection ties the sophist to his disciples’ “secret doctrines”? How can ‘Socrates’ attack the sophist with unfair criticisms, then defend his project as if he were the man himself, and finish accusing Protagoras’ “Truth” of being true to no one? This paper discusses these questions aiming to understand how can ‘Socrates’ sidestep ‘Protagoras’ without refuting him.